(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Because they offer easily available and captivating information to enhance listening comprehension, podcasts have completely changed the way people learn languages. This essay examines the many advantages of podcasting, as well as practical advice for optimizing their educational impact and successful integration tactics within language learning programs. Teachers may help students develop better listening skills and general language competency by using podcasts into their lesson plans